The Influence of Process Parameters on the Mechanical Properties of Friction Stir-Welded Dissimilar Aluminium Alloys AA2219 and AA7068. (29th March 2022) - Refaai, Mohamad Reda A.; Reddy, R. Meenakshi; Radha, A.; Christopher, David
Abstract : A practical solution is friction stir welding (FSW) of heterogeneous alloys in industrial applications. The welded joint's mechanical strength has been improved by combining two different alloys (AA2219 and AA7068). The focus of this study was on friction stir-welded heterogeneous metals' microhardness and material properties. It is possible to work with either hot or cold aluminium alloy, as it is heat treatable. Revitalizing and precipitation hardening follow the heat treatment. The welded joints' hardness was assessed in several locations. Different joints' tensile characteristics are compared. According to the stress-strain curve, the FSW settings' mechanical properties were spread throughout the material flow. In terms of tool profiles, the cylindrical threaded profile is critical. One-third of the efficiency is due to it. A 195 MPa strength was reached in the cylindrical threaded pin profiled tool. In a new study, researchers discovered that cylindrical threads have faster rotary motion, transversal, and D/d speeds. The cylindrical threaded tool provided the highest tensile strength and was superior to other materials. This phase of the material characterization included measurements of tensile strength and hardness.